Evaluation of a modified thromboelastography assay for the screening of von Willebrand disease - Topf, Hans-Georg; Weiss, Dominik; Lischetzki, Grischa; Strasser, Erwin; Rascher, Wolfgang; Rauh, Manfred (Thrombosis and Haemostasis, 2011)
Thromboelastography (TEG) has been shown to be a valuable point-of-care device for the rapid diagnosis of various bleeding disorders. However, TEG has thus far not been used for the screening for von Willebrand disease (VWD). We evaluated the performance of a modified TEG assay for the laboratory screening of VWD. Three hundred twenty-eight patients (148 male, 180 female, median age 8.4 years, range 0.1 – 72.7 years) were included in the study. The diagnosis and classification of patients was based on personal and familial case history, von Willebrand factor antigen, ristocetin cofactor levels, collagen binding assay, factor VIII coagulant activity and multimer analysis. The ratio of clot strength after preincubation with ristocetin, and without ristocetin, represents the component of clot strength that is formed by cross-linked fibrin fibres and is dependent on the agglutinated platelet fraction. The decrease of the maximum amplitude is a function of the ristocetin concentration and provides a diagnostic parameter able to differentiate between healthy individuals and patients having VWD. Based on a preliminary cut-off value of 25% for the area under the curve (AUC) ratio, the sensitivity varied from 53% to 100% for the different VWD patient groups. The test is suitable for use as a screening test using whole blood and has the additional benefit of being suitable as a point of care test. It appears also useful for monitoring responses to desmopressin (DDAVP) and infusion therapy.
Keywords: von Willebrand disease; von Willebrand factor; thromboelastography; Rotem; point of care